2004
DOI: 10.1002/ptr.1369
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of Hypericum perforatum L. on K562 erythroleukemic cells: differential effects between methanolic extract and hypericin

Abstract: The influence of a methanolic extract of Hypericum perforatum L. and of purified hypericin has been comparatively tested on the growth of a human erythroleukemic cell line (K562). After 1 h exposure to increasing concentrations (as hypericin content) of both agents in the dark, leukemic cells were grown for 24 h and 48 h. The effects on cell growth were determined by viable cell count, flow cytometry analysis and fluorescence microscopy. Our data show that purified hypericin has only a weak inhibitory effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…It is even considered as a bridge between the conventional and the alternative medicine (Istikoglou et al, 2010;Klemow et al, 2011). Different extracts of this plant are reported to induce growth arrest of malignant cells, such as leukemia, melanoma, prostate, and breast cancer cells (Ferguson et al, 2011;Hostanska et al, 2002Hostanska et al, , 2003Martarelli et al, 2004;Menichini et al, 2013;Roscetti et al, 2004). Two major biologically active constituents have identified: hyperforin and hypericin (Hostanska et al, 2003;Klemow et al, 2011).…”
Section: Herbsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is even considered as a bridge between the conventional and the alternative medicine (Istikoglou et al, 2010;Klemow et al, 2011). Different extracts of this plant are reported to induce growth arrest of malignant cells, such as leukemia, melanoma, prostate, and breast cancer cells (Ferguson et al, 2011;Hostanska et al, 2002Hostanska et al, , 2003Martarelli et al, 2004;Menichini et al, 2013;Roscetti et al, 2004). Two major biologically active constituents have identified: hyperforin and hypericin (Hostanska et al, 2003;Klemow et al, 2011).…”
Section: Herbsmentioning
confidence: 99%
“…This compound might be an attractive broadspectrum anticancer reagent with activity against a wide range of different tumors (Billard et al, 2013;Klemow et al, 2011;Schempp et al, 2002). The other active constituent isolated from H. perforatum, hypericin, can also inhibit the growth of cells derived from a variety of neoplastic tissues; activity of this compound is attributed to its photocytotoxic properties and hypericin can be used as a component of photodynamic therapy (Hostanska et al, 2002;Klemow et al, 2011;Menichini et al, 2013;Ocak et al, 2013;Roscetti et al, 2004). Both compounds can work also in cooperation, to impede the growth of malignant cells synergistically, making H. perforatum an interesting option in cancer treatment and clearly warranting further investigations to evaluate their action (Hostanska et al, 2003;Klemow et al, 2011).…”
Section: Herbsmentioning
confidence: 99%
“…One such agent is hypericin (HY;1,3,4,6,8,10,9,perylene-7,14-dione; Falk, 1999), a secondary metabolite that can be isolated from the plant Hypericum performatum, commonly known as St. Johns wort. Because of its photoactive properties and low cytotoxicity, attention has been focused on its application in PDT (Okpanyi et al, 1990;Kersten et al, 1999;Agostinis et al, 2002;Roscetti et al, 2004;Kiesslich et al, 2006). Apoptosis and necrosis are two kinds of PDT-induced cell death (Fiers et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A known flavonoid rutin was isolated by us (unpublished data). A large number of reports are available on the antitumor properties of hypericin (Roscetti et al, 2004;Chen et al, 2002). Hence, the observed antitumor properties of the MEHH may be due to the presence of hypericin and other phytoconstituents of MEHH.…”
Section: Discussionmentioning
confidence: 99%
“…Vinca alkaloids, epipodophyllotoxins, taxanes and camptothecins are the four main classes of anticancer agents from plants currently in clinical use and natural products isolated from medicinal plants can remain as essential components in the search for new medicines (Balunas and Kinghorn, 2005) The genus Hypericum encompasses various species used in traditional medicine in different parts of the world. Strong cytotoxic and anticancer properties have been observed in H. perforatum (Roscetti et al, 2004), H. mysorence, H. patulum (Vijayan et al, 2003b, H. polyanthemum (Ferraz et al, 2005), H. drummondii (Jayasuriya and McChesney, 1989) and several other plants of the genus Hypericum (Ferraz et al, 2005) and many of their phytoconstituents. Earlier studies carried out in our laboratories have indicated the potent cytotoxic nature of H. hookerianum against several cancerous cell lines.…”
mentioning
confidence: 99%